2014
DOI: 10.1590/1983-084x/12_035
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade antioxidante e inibição da tirosinase do extrato das folhas do jatobá (Hymenaea stigonocarpa Mart. ex Hayne)

Abstract: Determination of total phenol, antioxidant activity and inhibition by tyrosinase extract of jatobá (Hymenaea stigonocarpa Mart. ex Hayne) leaves. The jatobá species, also known as Brazilian cherry, are traditionally used for the treatment of various diseases. Chemotaxonomic studies have described the Hymenaea genus as a potential source of phenolic compounds, tannins and flavonoids, which have antioxidant activity, thus being potential inhibitors of tyrosinase, which is the enzyme responsible for skin pigmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In its proximate composition, jatobá-do-cerrado and jatobá-da-mata in g/100 g on a dry basis have on average: 7.60 ± 0.22 and 8.37 ± 0.12 g/100 g, lipids of 3, 03 ± 0.05 and 2.92 ± 0.11 g/100 g, ash of 4.60 ± 0.06 and 5.48 ± 0.07, soluble dietary fiber of 11.01 ± 0.50 and 9.81 ± 0.58 g/100 g, insoluble dietary fiber of 42.86 ± 0.27 and 45.79 ± 0.61 g/100 g and carbohydrates of 18.54 ± 0.55 and 20.18 ± 0.46 g/100 g, respectively (SILVA et al, 2001). The genus Hymenaea is recognized as a source of phenolic compounds, and research has suggested that its antioxidant activity is related to polyphenol and flavonoid presence (MIRANDA et al, 2014).…”
Section: Characterization Of Native Fruits For Developing New Productsmentioning
confidence: 99%
“…In its proximate composition, jatobá-do-cerrado and jatobá-da-mata in g/100 g on a dry basis have on average: 7.60 ± 0.22 and 8.37 ± 0.12 g/100 g, lipids of 3, 03 ± 0.05 and 2.92 ± 0.11 g/100 g, ash of 4.60 ± 0.06 and 5.48 ± 0.07, soluble dietary fiber of 11.01 ± 0.50 and 9.81 ± 0.58 g/100 g, insoluble dietary fiber of 42.86 ± 0.27 and 45.79 ± 0.61 g/100 g and carbohydrates of 18.54 ± 0.55 and 20.18 ± 0.46 g/100 g, respectively (SILVA et al, 2001). The genus Hymenaea is recognized as a source of phenolic compounds, and research has suggested that its antioxidant activity is related to polyphenol and flavonoid presence (MIRANDA et al, 2014).…”
Section: Characterization Of Native Fruits For Developing New Productsmentioning
confidence: 99%